Comparing the environmental sustainability of two gold production methods using integrated Emergy and Life Cycle Assessment. (December 2019) - Cano Londoño, Natalia A.; Velásquez, Héctor I.; McIntyre, Neil
Highlights: Critical assessment of the applicability of emergy accounting to alternative gold mining methods. Mines exhibit low apparent sustainability because of emergy demands of non-renewable resources. A new method of integrating emissions into emergy worsens the apparent sustainability of the mines. Abstract: Emergy analysis and combined emergy and Life Cycle Assessment (EM-LCA) were used to evaluate the sustainability of an open-pit gold mine and an alluvial gold mine in Colombia. The emergy is the work done to support the gold production separated into renewable and non-renewable energy, and also into those associated directly with the mining and those due to imported resources. The EM-LCA is a new extension of emergy that incorporates the work done by the environment to assimilate airborne and waterborne pollutants. Emergy Sustainability Index values <1 indicate an unsustainable practice, those between 1 and 5 indicate a sustainable contribution in the medium term but not necessarily in the long term, and those >5 can be considered sustainable. The open-pit and alluvial mines were found to have Emergy Sustainability Index values of 0.02 and 0.04 respectively using emergy accounting, and 0.002 and 0.035 using EM-LCA. The low values from the emergy analysis are mainly due to the large amount of imported resources required by the gold production. The open-pit mine uses a more highly industrialized process and hence relies more on imported resources and less on renewable resources. Open-pit mining also generates more emissions hence its comparatively low EM-LCA rating. The results demonstrate the need to implement management policies that encourage a higher dependence on renewable resources and to reduce reliance on imported resources, as well the need for technologies that lower emissions. It is also concluded that the novel EM-LCA approach has the potential to extend emergy analysis to incorporate emissions. The study also highlights the limitations of emergy accounting for coherent assessment of mining projects.